FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK SKINCARE MS GLOW DI KOTA MALANG - Widi Dewi Ruspitasari (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2022)
This study aims to determine the factors that influence purchasing decisions. The research method uses a quantitative approach with Accidental Sampling sampling technique, a total of 100 respondents using Ms Glow skincare products. From this study, it was found that the celebrity endorser variable had a positive but not significant effect on purchasing decisions for Ms glow skincare products in the city of Malang. Product quality variable has a positive but not significant effect on purchasing decisions for Ms glow skincare products in the city of Malang. Product review variables have a significant positive effect on purchasing decisions for Ms glow skincare products in the city of Malang. Skincare entrepreneurs need to pay attention to the artists used in Celebrity endorsers, because the artists used must really match the criteria for the products to be offered. Keywords: Product Quality, Celebrity Endorsers, Product Reviews, and Purchase Decisions.